2016
DOI: 10.1038/srep38995
|View full text |Cite|
|
Sign up to set email alerts
|

Spring maize yield, soil water use and water use efficiency under plastic film and straw mulches in the Loess Plateau

Abstract: To compare the soil water balance, yield and water use efficiency (WUE) of spring maize under different mulching types in the Loess Plateau, a 7-year field experiment was conducted in the Changwu region of the Loess Plateau. Three treatments were used in this experiment: straw mulch (SM), plastic film mulch (PM) and conventional covering without mulch (CK). Results show that the soil water change of dryland spring maize was as deep as 300 cm depth and hence 300 cm is recommended as the minimum depth when measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 26 publications
(46 reference statements)
4
12
0
Order By: Relevance
“…Compared with the three mulching modes, non-mulching treatment generally produced a slightly high crop water use, but the difference was not significant among the four modes. These results are in good agreement with the findings by Lin et al (2016), who observed no significant differences in crop water use among different mulching modes. At the early growth stage, dryland maize plants were smaller and the consumption of water was mainly via soil evaporation.…”
Section: Crop Water Use and Water Use Efficiency (Wue)supporting
confidence: 93%
“…Compared with the three mulching modes, non-mulching treatment generally produced a slightly high crop water use, but the difference was not significant among the four modes. These results are in good agreement with the findings by Lin et al (2016), who observed no significant differences in crop water use among different mulching modes. At the early growth stage, dryland maize plants were smaller and the consumption of water was mainly via soil evaporation.…”
Section: Crop Water Use and Water Use Efficiency (Wue)supporting
confidence: 93%
“…A similar effect was noted by Bogunović et al (2018b) RT has a similar negative effect on crop yield as no-tillage (Pittelkow et al, 2014) which can be noted at bare plots in this study, but reduced tillage systems MT and RT with straw mulch resulted in higher yield (25%; 20%) in comparison to plots without straw (Figure 8). This effect has been noticed by Dossou-Yovo et al (2016) and Lin et al (2016). Also, straw cover provided 15% higher yield (Figure 8).…”
Section: Soybean Yieldsupporting
confidence: 55%
“… 27 and Lin et al . 37 , who attributed their results to surface cover and improvements in rainwater harvesting and soil moisture conservation, and the shading effect of the canopy under a mulch was greater than under CK. Our results demonstrated that among the various mulch treatments, RFPS gave the maximum yield and WUE, followed in the order by FPP and FPS, with all differences being significant ( P < 0.05) (Tables 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%